(untitled) (Research, Society and Development, 2023)
Objective: to report the experience of an extension activity carried out during Graduation, whose objective was to promote the mental health of elderly people through a workshop on art therapy practices combined with music therapy. Methodology: This is a descriptive study, of the experience report type, carried out based on the student practice of the Integrative and Complementary Practices in Health (PICS - Práticas Integrativas e Complementares em Saúde) discipline. The group was sensitized about Art Therapy and, subsequently, the participants were divided into groups and given mandalas and painting materials. Slow, relaxing music was used to accompany the therapeutic practice, in order to provide a setting for introspection. Results: the elderly were placed in groups, where there was an exchange of experiences and, from this, the construction of interpersonal relationships. As a result, a satisfactory return was obtained on the theme of group interaction, which is fundamental for increasing the availability of social resources for the elderly and, consequently, alleviating the symptoms of loneliness. Music was made available to provide relaxation to the elderly, and it was noticed that, once exposed to relaxing music, the elderly concentrated more on the task. It was possible to observe small impasses related to the fine motor coordination necessary for painting the mandalas, which is justified by the physiological deterioration of the muscles due to age. Conclusion: the performance of the activity is considered satisfactory, as it encourages relaxation and exchange of experiences between participants, in addition to inserting PICS as a tangible theme in their lives.